Graphic User Interface (GUI) Matlab for Making Media Teaching Media Straight Motion Physics - Muhammad Nasir; Prio Sigit Nugroho; S. Ratih Uswatun Khasanah; Hafiz Suhendra (Universitas Pendidikan Mandalika, 2022)
The purpose of this study was to analize he use of GUI Matlab as a medium for learning physics for students at the SMP/MTs and SMA/SMK/MA levels through literature study. The method used is a literature study and development research with a 4D approach (define, design, develop, and dessimenate), but this research has only reached the development stage. The results obtained are that a physics calculator has been made for GLB and GLBB materials that can be used in calculating questions with the calculation results in accordance with manual calculations. In addition, based on the existing literature, the Matlab GUI can be used as a learning medium for straight motion physics subjects.